Chitin estimation in agricultural soils - Alex Gobbi; Roberto Lava; Giorgia Vianello (EFSA Journal)
Abstract The present scientific report has been elaborated in the context of the European Commission mandate requesting for an opinion according to Article 23(6) of Regulation (EC) No 1107/2009 regarding the approved plant protection uses of chitosan and chitosan hydrochloride as basic substances. This scientific report focused on estimating the amount of chitin present in an average agricultural soil, aiming to establish a baseline for its natural availability. Understanding the source and concentration of biotic chitin in soil assisted the estimation of chitosan potentially available in the environment, as requested in one of terms of reference of the concerned EC mandate. Chitin in soil was estimated to range from 27 to 280 kg/ha in the first 0–5 cm layer and 99 to 901 kg/ha in the 0–20 cm layer. Fungi are the main chitin producer followed by insects and nematodes. Soil crustaceans could not be considered in the assessment due to the lack of necessary information and the variability of their presence. The development of a polynomial function to estimate the amount of chitin in such biome can also identify the main predictors of chitin content in similar biomes. This estimate was based on the available scientific literature, and it would require additional validation using field measurements and error analysis on different soil types and conditions, to become a generalised model. Lack of information alongside related uncertainties have also been identified.